Designing an app for alternative access assessments: Using interviews to uncover and define user needs. - Koester, Heidi; Fager, Susan; Sorenson, Tabatha; Jakobs, Erik (Assistive Technology, 2024)
To support effective alternative access assessment and service delivery for people with motor impairments, we are developing an app called Access Navigator. This paper describes the first stage of the project: the interviews we conducted as part of a discovery process to improve our understanding of user needs. We individually interviewed 8 assistive technology practitioners and 3 clients who use alternative access methods, to learn what practitioners were currently doing in their access assessments, identify opportunities for improving current practice, and understand what the assessment process was like for clients. We extracted 236 relevant quotes from interview transcripts, and clustered the quotes using the affinity wall method, yielding 42 themes. Here we present the 21 highest priority themes, along with the app requirements that support those themes. Results confirmed the need for a tool to support more effective assessments, with emphasis on taking the worry out of access assessments and supporting early success. Results also revealed specific needs such as flexible workflow, personalized test-drive tasks, and a choice of metrics (including client preference). With a richer understanding of user needs, we are in a much better position to design software that can address those needs.